Waqf Literacy, Trust, and Public Interest in Cash Waqf Postcolonial: A Study of Urban Muslims in Jakarta - Hendra Kholid; Ade Suherlan (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2026)
This study examines the determinants of public interest in participating in cash waqf in Jakarta by focusing on the roles of waqf literacy, trust in waqf management institutions, and religiosity within a postcolonial urban context. Employing a quantitative approach, data were collected from 350 respondents and analyzed using descriptive statistics and multiple linear regression. The results show that public interest in cash waqf is relatively high (Mean = 3.50; SD = 0.75), while waqf literacy remains at a moderate level (Mean = 3.20; SD = 0.85) and trust in waqf management institutions is comparatively lower (Mean = 2.90; SD = 0.95), indicating a significant but underutilized participation potential. The regression model demonstrates strong explanatory power, accounting for 55% of the variance in public interest (R² = 0.550; Adjusted R² = 0.540; F = 58.320; p < 0.001). Waqf literacy has a positive and significant effect on public interest (B = 0.350; β = 0.280; p < 0.001), while trust in waqf management institutions emerges as the most dominant determinant (B = 0.450; β = 0.390; p < 0.001). Religiosity also exerts a significant but weaker influence (B = 0.200; β = 0.180; p = 0.008), whereas income and education show moderate effects, and age and gender are not statistically significant. The findings suggest that cash waqf participation in Jakarta is shaped less by demographic factors and more by epistemic capacity and institutional legitimacy. Theoretically, this study contributes to contemporary waqf scholarship by demonstrating that Islamic piety in postcolonial urban societies is not diminished but renegotiated through literacy and trust. It argues that normative–theological explanations of waqf must be complemented by epistemic and governance perspectives to understand modern Islamic philanthropic practices adequately.